Confidence and motivation to teach primary physical education: A survey of specialist primary physical education pre-service teachers in Australia - Spittle, Sharna; Spittle, Michael; Encel, Kim; Itoh, Sho (Frontiers in Education, 2022)
This study explored confidence and motivation to teach physical education of pre-service teachers specialising in primary school physical education. Participants were 277 pre-service teachers with a mean age of 21.37 years (SD = 3.09) enrolled in a Bachelor of Education (P-12) who were specialising in primary physical education (P-6). Pre-service teachers completed the Confidence and Motivation to Teach Primary Physical Education Questionnaire (CMTPPEQ), which measures confidence (management and planning and implementation) and intrinsic, extrinsic, and amotivated types of motivation (knowledge, performance, practice, professional expectations, student outcomes, and disengagement) towards teaching primary school physical education. Pre-service teachers reported higher confidence in implementation and higher motivation in practice and performance, with very low disengagement. Pre-service teachers in first-year were significantly less confident in both management and planning and implementation than other year levels (p<.05). Pre-service teachers with less training and experience (completed no units in physical education or who had taught less than one hour of physical education on teaching rounds) were significantly less confident in both management and planning and implementation (p<.05). Pre-service teachers reported higher intrinsic motivation for practice and extrinsic motivation for performance, with males reporting significantly higher extrinsic motivation in professional expectations than females (p<.05). The study has highlighted the confidence of pre-service primary physical education specialist teachers in implementing physical education, but lower confidence in management and planning. A practical implication from the findings is the importance of training and experience in developing confidence and motivation, even for those specialising in physical education.